Implementation of a Multicriteria Analysis Model to Determine Anthropometric Characteristics of an Optimal Helmet of an Italian Scooter. - Cuevas, Josué; Ochoa, Alberto; Hernandez Arellano, Juan Luis; Mejia, Jose; Mederos, Boris (2020)
At the beginning of the sixties, the Italian scooters became popular in Italy, an age that was considered unimportant the safety of people. However, safety standards are now stronger, and helmet use is mandatory in most countries. That is why this paper try to analyze in greater detail the characteristics associated with the anthropometric measurements of a representative sample of a broader society for determining the ideal characteristics of a helmet associated with this type of vehicle. For this reason and considering the relevance of our study to a Smart City, we will use a multicriteria analysis and an intelligent data analysis in order to understand much better the ideal and suitable measurements to be able to design a helmet for an Italian scooter.